The paradox of information : the significance of electronic media / Nik 'Atiqah Fayyadhah Nik Zamri and Nur Fatin Shahirah Tajuddin - Nik Zamri, Nik 'Atiqah Fayyadhah; Tajuddin, Nur Fatin Shahirah (Faculty of Information Management, 2015)
This article was created with the purpose to discuss about the paradox of electronic media. Types, roles, importance and affecting of electronic media in our culture and society are those included in this article. There are also consists the problem arise in handling electronic media to deliver information to the public. From the research, the existing of information technology makes the people know the type's electronic media and the paradox occur in delivering information. This article states the response received from the user when there are problem occurs in receiving information through electronic media such as server down and network connection not discover at everyplace.